Synthesis and dopaminergic activity of a series of new 1-aryl tetrahydroisoquinolines and 2-substituted 1-aryl-3-tetrahydrobenzazepines. - Lucena-Serrano, Cristina; Lucena-Serrano, Ana; Rivera-Ramírez, Alicia; López-Romero, Juan Manuel; Valpuesta-Fernández, María; Díaz-Morilla, Amelia (Elsevier, 2018)
A series of new 1-aryl-6,7-dihydroxy tetrahydroisoquinolines with several substitution patterns in the 1-aryl group at C-1 were prepared in good yields. The influence of each substituent on the affinity and selectivity for D1 and D2 dopaminergic receptors was studied. Moreover, N-alkyl salts of these tetrahydroisoquinolines were used as starting material to synthesize a series of new 1-aryl-7,8-dihydroxy 3-tetrahydrobenzazepines derivatives with electron-withdrawing substituents at C-2 position by the diastereoselective Stevens rearrangement. The structure-activity relationship of these compounds was explored to evaluate the effect of the functional group at C-2 in benzazepines and the modification in the aryl group at the isoquinoline C-1 position towards the affinity and selectivity for the mentioned receptors. The 1-aryl-6,7-dihydroxy tetrahydroisoquinoline 4c shows significant affinity towards D2 receptor, with Ki value of 31 nM. This significant affinity can be attributed to the presence of a thiomethyl group, and it is the most active 1-aryl-6,7-dihydroxy tetrahydroisoquinoline derivative reported to date.
Keywords: Dopamina - Receptores; Química biorgánica; Tetrahydroisoquinolines; 3-tetrahydrobenzazepines; Stevens rearrangement; Dopamine receptors; Binding